THE PARADOX OF PROGRESS: AI SUPREMACY, SPIRITUAL CRISIS, AND AN ATTEMPT AT RECONCILIATION - Ana Maulida Sabila; Benny Prasetya; Khoiriyah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This research is motivated by the fact that today’s civilization has entered a post-normal era characterized by complexity, chaos, and contradiction. This research aims to look at the other side of scientific and technological advances that impact the dimension of human spirituality. This research adopts a qualitative design, where all data sources are obtained from related literature and analyzed using content analysis techniques. The findings reveal that the supremacy of artificial intelligence (AI) is paradoxical, offering various conveniences on the one hand, but harboring a ‘dark side’ that can harm humans. When viewed from an Islamic perspective, AI has the potential to lead to the alienation of spirituality that can reduce the role of humans and their relationship with God. A possible reconciliation of Islam and AI depends on developing and applying AI ethically while prioritizing humanity and Islamic values.